O direito de ter direitos : o Ministério Público como mediador das terras de remanescentes de quilombos do município de Poconé-MT - Silva, Maurício Marinho da (2020)
The purpose of this current work is to understand the role and the action of the Ministério Público Federal de Mato Grosso on mediating the regularization processes of quilombo remnants lands located in the municipality of Poconé. It is observed that after the publication of Constituição Federal de 1988, there is a guaranteed quilombola document property through article 68 of Ato das Disposições Constitucionais Transitórias (ADCT) and, having passed 32 years, the quilombola issue is still unresolved, which concerns the realization of their land rights. In Mato Grosso, there are 73 administrative processes pending at the Regional Superintendence of the Superintendência Regional do Instituto Nacional de Colonização e Reforma Agrária (INCRA), awaiting for promotion of land tenure regularization of their remnants quilombo, in their different procedural phases, but none has been concluded yet. Accordingly, through a ethnography documentary of the processes and procedures present in the Ministério Público. The study analyze the judicial and extrajudicial contents of the administrative processes for the regularization of quilombola lands, looking for actions and associations registered in the pages of the official and administrative acts, emphasising three Remaining Communities Quilombos of Poconé: Campina de Pedra, Laranjal and Chumbo. The Ministério Público Federal as institution with an identifiable identity rules, institutional attributions, function and mission presented itself as prescribed by Constituição de 1988 justifying its action to protect and guarantee the rights of quilombola communities, conferred after the period of redemocratization which gave administrative authority and corpus functional independence, protected by norms and prerogative forces in the Rule of Law Democracy. Apparently, it has made efforts to ensure the right of land realization of the CRQs of Poconé, however as one of the state powers, the Ministério Público, despite its engagement and commitment with the Quilombos Remnants, is limited by the other powers, the explicit (Executivo, Legislativo, Judiciário) and implicit, reproducing our colonial heritage and which has racism as a structural element, which prevent full enjoyment of fundamental rights through public policies and public resources for quilombola population.